Two sides of the same coin? Unraveling subtle differences between human embryonic and induced pluripotent stem cells by Raman spectroscopy - Parrotta, Elvira (Stem Cell Res Ther, 2017)
BACKGROUND: Human pluripotent stem cells, including embryonic stem cells and induced pluripotent stem cells, hold enormous promise for many biomedical applications, such as regenerative medicine, drug testing, and disease modeling. Although induced pluripotent stem cells resemble embryonic stem cells both morphologically and functionally, the extent to which these cell lines are truly equivalent, from a molecular point of view, remains controversial. METHODS: Principal component analysis and K-means cluster analysis of collected Raman spectroscopy data were used for a comparative study of the biochemical fingerprint of human induced pluripotent stem cells and human embryonic stem cells. The Raman spectra analysis results were further validated by conventional biological assays. RESULTS: Raman spectra analysis revealed that the major difference between human embryonic stem cells and induced pluripotent stem cells is due to the nucleic acid content, as shown by the strong positive peaks at 785, 1098, 1334, 1371, 1484, and 1575 cm(–1), which is enriched in human induced pluripotent stem cells. CONCLUSIONS: Here, we report a nonbiological approach to discriminate human induced pluripotent stem cells from their native embryonic stem cell counterparts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-017-0720-1) contains supplementary material, which is available to authorized users.